Pedagogical foundations of linguistic education at the university - Жиренов, Саян (Pedagogy and Psychology, 2022)
The article describes in detail the scientific, theoretical and methodological issues of linguistic education in a higher educational institution. The research work was carried out within the framework of the fundamental research project of the Kazakh National Pedagogical University named after Abai for young researchers 2022 RN: 0122RKI0048 – «Cognitive-conceptual foundations of the lexical system of the Kazakh language». The issue of language education in higher education is one of the most pressing pedagogical issues today. Linguistic education is one of the most important factors in increasing the intellectual potential of a future specialist, shaping personality and strengthening language competence. The pedagogical basis of linguistic education in a higher educational institution is considered not only as a means of communication for a future specialist, but also from the point of view of a cultural, cognitive, professional, grammatical, rhetorical, pedagogical, social phenomenon of language. In the formation of personality, the development of the applied side of the language on the pedagogical basis of linguistic knowledge, the development of vocabulary, the development of professional speech skills, and the features of the rational use of language etiquette in a communicative environment are widely considered.